2015
DOI: 10.1111/jth.12919
|View full text |Cite
|
Sign up to set email alerts
|

Early hemostatic responses to trauma identified with hierarchical clustering analysis

Abstract: Background Trauma-induced coagulopathy is a complex multifactorial hemostatic response that is poorly understood. Objectives Identify distinct hemostatic responses to trauma and identify key components of the hemostatic system that vary between responses. Patients/Methods Cross-sectional observational study of adult trauma patients at an urban Level I trauma center Emergency Department. Hierarchical clustering analysis was used to identify distinct clusters of similar subjects using vital signs, injury/sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…Original work on trauma-induced coagulopathy hypothesized that both tissue injury and shock were necessary for driving this process (24), which appeared to be validated in an animal model(25). However, with the emergence of unique phenotypes of TIC(26) in the context that alteration in clot formation does not correlate with alteration in clot degradation (3, 4), implications of coagulation abnormalities beyond protein C is evident.…”
Section: Discussionmentioning
confidence: 99%
“…Original work on trauma-induced coagulopathy hypothesized that both tissue injury and shock were necessary for driving this process (24), which appeared to be validated in an animal model(25). However, with the emergence of unique phenotypes of TIC(26) in the context that alteration in clot formation does not correlate with alteration in clot degradation (3, 4), implications of coagulation abnormalities beyond protein C is evident.…”
Section: Discussionmentioning
confidence: 99%
“…The calibration and goodness of fit of the logistic regression models were evaluated using the χ 2 Hosmer-Lemeshow (HL) test, and model discrimination was assessed by means of area under the receiver operating characteristic curve (AUROC). Correlations Duration of critical care stay (days)* 3 (2-5) 7 (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) 20 (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27) 36 (32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47) 11 (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] Furthermore, it should be noted that the addition of thrombomodulin in thrombin generation assays can prolong the lag time and decrease the peak and endogenous-thrombin potential, 13,14 which may regulated by cell surfaces rather than enzymatic protein and protease reactions and consumptive pathologies alone, and the robust data generated by independent groups of investigators using hierarchical clustering analyses to identify heterogeneity in phenotypes of clot formation and lysis in trauma populations. [20][21][22] Specifically, these clustering analyses have confirmed that not all phenotypes of TIC can be explained by clotting factor changes or solely mediated by thrombin.…”
Section: Thromb Inmentioning
confidence: 68%